Conceptualizing digital transformation using semantic decomposition - Rojas-Segura, Javier (2023)
Economic and social disruption generated by COVID-19 increased research on digital transformation processes; however, consensus about the formal conceptual definition of digital transformation is yet to be reached. A concise and clear concept built using existing definitions in literature is needed for empirical research in the business and management fields. Using semantic decomposition method to systematically decompose the extant definitions collected from the business literature, this study proposes the following formal conceptual definition of digital transformation: “a process that aims to improve society by triggering significant changes to the enterprise business model using digital technologies”. Consistent measurable properties caused by a formal conceptual definition support academic research and enable practitioners to exploit new knowledge essential when adapting the firm’s business model to the new digital reality.